Corporate Governance and Financial Transparency: A Legal Perpective on Reducing Fraud in Global Financial Markets - Utama, Ahmad Nur Budi; Purwoko, Bambang (IJBLE Scientific Publications Community Inc., 2024)
This study explores the role of corporate governance and financial transparency in reducing fraud within global financial markets from a legal perspective. Through an analysis of case studies and regulatory frameworks, it examines how robust governance mechanisms—such as independent boards, effective audit committees, and clear separation of CEO and chair roles—enhance financial transparency and accountability. Legal reforms, including the Sarbanes-Oxley Act, have proven effective in reducing fraud in developed markets but highlight enforcement challenges in emerging economies. The study also discusses emerging trends such as the integration of ESG criteria and the adoption of technologies like blockchain and AI, which offer new opportunities to improve transparency and governance. The findings suggest that a multi-faceted approach combining legal reforms, technological innovation, and cultural alignment is essential for building a resilient and trustworthy global financial system.